PENGARUH KINERJA KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN JASA TRANSPORTASI YANG TERDAFTAR DI BEI - Sari, Dyah Ratna; Retnaningdiah, Dian (Journal Competency of Business, 2021)
In Indonesia, the development of the business world has become increasingly widespread which has resulted in increasingly fierce business competition. The performance of a company is assessed by using financial ratios. The purpose of this study is to determine the effect of financial performance on Profit Growth in Transportation Service Companies listed on the Indonesia Stock Exchange. This study employed a quantitative approach, the samples used were 4 transportation service companies listed on the Indonesia Stock Exchange, the data collection technique used was secondary data obtained from the company's website. The hypothesis testing shows that the current ratio has no significant effect on profit growth, which meansthat a high current ratio value may not necessarily increase company profits. The total asset turnover (TATO) has no significant effect on profit growth. This indicates that a high TATO means thatthe company only uses a few assets. The debt-to-equity ratio (DER) has a significant effect on profit growth.This shows that the higher the DER value, the riskier the company is. The net profit margin (NPM) has no significant effect on profit growth, which indicates that a high NPM value means the company can generate high net income as well.